Dampak Pengembangan Pariwisata di Pantai Ancol - Rizki Nurul Nugraha; Ananda Fadila Putri (Jurnal Ilmiah Wahana Pendidikan, 2023)
DKI Jakarta Province has various types of tourist options that tourists can visit, ranging from recreational parks, shopping centers, events, culinary tourism, cultural tourism and marine tourism. DKI Jakarta Province is also an area with the largest number of museums and places of historical relics coupled with the implementation of various tourism attractions as well as arts and cultural activities. in several areas that have met the requirements to be categorized as “Tourism Destinations” North Jakarta, whose territory is located on the coast, has added value in developing attractive tourism potential, not only for the people of Jakarta, but also for the wider Indonesian community. The North Jakarta government issued "12 Routes of Coastal Tourism Destinations" to introduce North Jakarta's diverse tourism offerings, including cultural tourism, religious tourism, shopping-culinary tourism, water sports-recreational tourism and eco-tourism. Taman Impian Jaya Ancol (TIJA) has an area of 552ha, located in Ancol Village, Pademangan District, North Jakarta. This tourist area is bounded by the easternmost boundary of the Sunda Kelapa Harbor which is the western boundary, up to the westernmost boundary of the Tanjung Priok PLTU as the eastern boundaryOjek Online, Legal Position, Responsibility